Design, fabrication and optimization of shear test rig (double shear type) - Mohd Fakrul Radzi, Mohd Mawardzi (2008)
Shear stress-strain relationship is an important material property of sheet metals. The property is difficult to measure compared to a more commonly used tensile stress-strain relationship. The objective of this project is to design and fabricate a rig that can be used to measure shear stress-strain relationship and test its workability. The rig has to be mounted in a tensile test machine and utilise the machine capability of measuring load and displacement progression. The data of load versus displacement will have to be converted into shear stress-strain relationship based on an oblique parallelepiped deformation theory.